Bolsonarismo: o populismo autoritário em conflito com a democracia liberal constitucional brasileira - Mesquita Júnior, Oton Fernandes (2023)
This is academic research that studies and points out the reasons that led to the emergence of Bolsonarism and the implications of this sociopolitical phenomenon for Brazilian democracy. The study understands Bolsonarism as a populist movement with authoritarian tendencies and analyzes the historical and political conditions that allowed its rise, starting with the June 2013 protests, going through the study of Operation Car Wash and the impeachment of President Dilma Rousseff. It also analyzes the anti-politics, anti-PT sentiment, and resentment present in the country's political atmosphere during the 2018 elections. Next, the study aims to examine populism, authoritarianism, reactionary politics, militarism, and Olavism as present and intrinsic elements of Bolsonarism, as well as analyze other aspects that underpin the Bolsonarist belief system. The research aims to demonstrate that while in power, Bolsonarism compromised the functioning of oversight and control institutions using infralegal norms, especially presidential executive orders, in violation of the principle of separation of powers, and was in open conflict with Brazilian democracy, contributing greatly to the erosion of the existing constitutional order. Finally, it highlights the role of the Supreme Federal Court in democratic resistance against the authoritarian advances promoted by Bolsonarism from the perspective of militant democracy. The research is of the juridical-doctrinal type, based on deductive methodology, with the use of intensive literature review. The research is pure and qualitative in nature, with a descriptive and exploratory purpose.